2023
DOI: 10.1021/acs.langmuir.3c01518
|View full text |Cite
|
Sign up to set email alerts
|

Black Phosphorus-Doped Graphitic Carbon Nitride with Aromatic Benzene Rings for Efficient Photocatalytic Hydrogen Production

Mahmudul Hassan Suhag,
Hideyuki Katsumata,
Ikki Tateishi
et al.

Abstract: Graphitic carbon nitride (g-C3N4, abbreviated as g-CN) suffers from low visible-light-responsive photocatalytic efficiency. In this study, aromatic benzene rings and black phosphorus (BP) were successfully incorporated into g-CN photocatalysts (BP/A-CN), resulting in modified materials with improved properties. Structural analysis confirmed the successful integration of aromatic rings and BP into the g-CN framework, indicating the formation of a stable composite. Morphological characterization revealed that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…Notably, various strategies have been devised to improve the photocatalytic performance of g-C 3 N 4 , including metal/nonmetal doping, molecular doping, nanostructure engineering, and heterojunction formation. 41–46…”
Section: Introductionmentioning
confidence: 99%
“…Notably, various strategies have been devised to improve the photocatalytic performance of g-C 3 N 4 , including metal/nonmetal doping, molecular doping, nanostructure engineering, and heterojunction formation. 41–46…”
Section: Introductionmentioning
confidence: 99%
“…Combustion of fossil fuels causes problems such as energy crisis and environmental pollution . Exploring clean and sustainable energy sources to replace fossil fuels remains one of the most important challenges of this century. After years of hard work by scientists and researchers, photocatalytic H 2 production is considered to be an ideal strategy to overcome the aforementioned issues. However, exploring photocatalysts with low cost, high activity, and photostability is still the focus of this field. In addition, during the photocatalytic reaction process, the photocatalyzed electrons and holes shift to the upper layer of the photocatalyst to undergo redox reactions, which seriously affects the performance of the catalyst. , Therefore, enhancing charge separation is key to improving photocatalytic performance .…”
Section: Introductionmentioning
confidence: 99%
“…Some inherent characteristics of g-CN, especially low charge separation, poor quantum efficiency, and quick recombination rate of the photogenerated e − –h + pairs, decrease its visible-light-responsive photocatalytic efficiency. 43,44 To boost the photocatalytic activity of g-CN, some attempts have been focused such as by elemental doping, 45–47 molecular doping, 48 and coupling with other semiconductors, including metal oxides, 49–51 metal sulfides, 52,53 and others. 54,55 It was reported that ZCN composites showed excellent photocatalytic activity due to the appropriate band gap alignment of g-C 3 N 4 and ZnO.…”
Section: Introductionmentioning
confidence: 99%